BTS Army: Melampaui Narasi Stigmatisasi Identitas Perempuan Penggemar - Devi, Jasmine Floretta Vasthia (UI Scholars Hub, 2022)
Decades have passed, but female fans who like male idols are still stigmatized, judged, and reduced to exist in society and popular culture. This is also what happened to ARMY, fans of the male idol group BTS. The research uses a qualitative research methodology elaborated through a feminist perspective to discuss how ARMYs are stigmatized because of the perceived inferiority of women and the existence of male domination in society, and also their love for the male group, regarded as the subordinated male group within the circle of hegemonic masculinity. However, the stigma and gender stereotypes attached to them were successfully broken. As a female fan group, ARMY realizes that humans are essentially free creatures who always make choices in their lives that will shape them as authentic individuals. With this full awareness, they take action through fan labor practices and fan activism, which leads them to optimize Creative Power.